2017
DOI: 10.1039/c7bm00866j
|View full text |Cite
|
Sign up to set email alerts
|

Codelivery of sorafenib and GPC3 siRNA with PEI-modified liposomes for hepatoma therapy

Abstract: Hepatocellular carcinoma (HCC) is one of the most common malignancies imposing a serious threat to human health worldwide. To date, the effect of HCC chemotherapy has been limited due to drug resistance. Combination therapy of chemotherapeutic drugs and siRNA represents an emerging strategy that may improve anticancer effects by synergistic actions. The current study was aimed at achieving better HCC treatment via combination therapy, in which PEI-modified liposomes prepared by a thin-film hydration method wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
20
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(23 citation statements)
references
References 32 publications
3
20
0
Order By: Relevance
“…Sunitinib liposomes were tested, in combination with liposomal irinotecan against a PC12 neuroendocrine tumour [ 197 ] and in combination with vinorelbine liposomes, for the treatment of invasive breast cancer [ 198 ]. Sorafenib was co-encapsulated in liposomes with photocyanine [ 199 ], gadolinium [ 200 ], and siRNA [ 201 ]. Further studies with these formulations may clarify if such strategies have the potential to enhance suppression of tumour neovasculature.…”
Section: Future Directionsmentioning
confidence: 99%
“…Sunitinib liposomes were tested, in combination with liposomal irinotecan against a PC12 neuroendocrine tumour [ 197 ] and in combination with vinorelbine liposomes, for the treatment of invasive breast cancer [ 198 ]. Sorafenib was co-encapsulated in liposomes with photocyanine [ 199 ], gadolinium [ 200 ], and siRNA [ 201 ]. Further studies with these formulations may clarify if such strategies have the potential to enhance suppression of tumour neovasculature.…”
Section: Future Directionsmentioning
confidence: 99%
“…More recently, Zang and his group demonstrated that co-delivery of VEGF-siRNA and Sorafenib through pH-sensitive liposomes showed a synergistic effect in hepatocellular carcinoma [89]. Several other lipid-based NPs, along with other chemotherapeutics, are also being used for better antiangiogenic and antitumor therapy [90,91]. mTOR inhibitor like rapamycin and its analogs also proved their antiangiogenic capability.…”
Section: Lipid-based Nanoparticles For Antiangiogenic Therapymentioning
confidence: 99%
“…Small interfering RNA (siRNA) are known to specifically inhibit the expression of target genes without inflicting significant toxicity (Dykxhoorn & Lieberman, 2006 ; Yang & Zhang, 2012 ). Our expectation is that VEGF siRNA will inhibit VEGF expression (Feng et al., 2014 ) and thereby realize anti-angiogenesis in tumors (Sun et al., 2017 ). Therefore, the simultaneous delivery of chemotherapy drugs and VEGF siRNA for cancer therapy is expected to hold particular promise as a potentially useful dual-modality approach for treating highly vascularized tumors such as NSCLC.…”
Section: Introductionmentioning
confidence: 99%